CpG Island Methylation of Suppressor of Cytokine Signaling-1 Gene Induced by HCV Is Associated With HCV-Related Hepatocellular Carcinoma - Liu, Miao; Du, Lingyao; Cheng, Xing; Yuan, Man; Shang, Jin; Shi, Ying; Yang, Hailing; Tang, Hong (Frontiers in Microbiology, 2022)
Suppressor of cytokine signaling 1 (SOCS-1) is implicated in both virus infection and carcinogenesis. This study investigated the role of HCV infection on SOCS-1 in normal and HCV infected tissues and reveals a possible mechanism underlying HCV induced hepatocellular carcinoma (HCC) genesis. In total, 10 HCV-HCC tissues, 7 adjacent tissues, 7 distal tissues and 16 normal liver tissues were collected. SOCS-1 expression in tissue sections was detected by immunohistochemistry. After viral load was quantified, correlation between SOCS-1 expression and viral load was analyzed in different tissues. Then HCV replicon model was used to detect relationship between HCV and SOCS-1. Afterwards, methylation specific PCR (MSP) was applied to show the methylation status of SOCS-1 genes in normal tissues and HCV replicon cells. Correlation between gene methylation, SOCS-1 expression and HCV were analyzed. The lowest expression of SOCS-1 was observed in HCV-HCC tissues. Tissues with a higher HCV viral load showed lower SOCS-1 expression (p=0.0282). Consistently, SOCS-1 mRNA and protein were lower in HCV replicon cells than in un-infected one. Furthermore, gene methylation was found in all examined tissues but higher in HCC tissues, and it is positively correlated with HCV viral load (r2=0.7309，p＜0.0001). HCV infection would up-regulate methylation of SOCS-1 gene in HCV replicon cells. The down-regulation of SOCS-1 in normal and HCV replicon cells may result from HCV infection through epigenetic regulation, in which gene methylation in CpG island of SOCS-1 promoters upon HCV infection suppress its expression.